Separation of 6-gingerol in zingiber officinale rubrum varieties using an ultrasonic assisted extraction method - Herliati Rahman; Satrio Nur Prambudi; Wahyu Endranaka (Jurnal Rekayasa Proses, 2021)
Gingerol is a chemical compound found in red ginger, with pharmaceutical use as an analgesic drug. Generally, gingerol separation in ginger uses the Soxhlet extraction method, but this process has a weakness. It requires a long process and unsatisfactory yield. This research aims to study ultrasonic frequency effect on increasing gingerol yield in the extraction process. The variables studied were extraction times with variations of 30, 60, 90, and 120 minutes. In addition, the ultrasonic effect was also observed with variations in the ultrasonic frequency of 40 and 50 kHz compared to the solvent extraction method. This study used 70% (v/v) ethanol as a solvent and an operating temperature of 50 ºC as fixed variables. Furthermore, it used a rotary vacuum evaporator at a pressure of 350 mmHg to separate the resulting gingerol extract. Qualitative sample analysis used Thin Layer Chromatography (TLC) and scanning electron microscope (SEM) while quantitative analysis used high-performance liquid chromatography (HPLC), Waters Alliance e2695 brand with X-Terra RP18 column 100 x 4.6 mm, five μm to determine the total gingerol extract. The results showed that ultrasonic power had a significant effect on the results obtained, with the highest yield was 24.71% at the ultrasonic frequency of 50 kHz with an extraction time of 120 minutes.